Impact of social interactions in the community on the transmission of tuberculosis in a high incidence area. Issue 2 (1st February 1999) - Classen, Collette N; Warren, Robin; Richardson, Madeleine; Hauman, John H; Gie, Robert P; Ellis, James H P; van Helden, Paul D; Beyers, Nulda
Abstract : BACKGROUND: Tuberculosis (TB) is transmitted by close contact with an infectious person. It is assumed that close contact occurs amongst household members and that contact outside the house is "casual" and does not play a major role in the transmission of TB. METHODS: This study was conducted in an impoverished area with a high incidence of TB and a low HIV seropositive prevalence. Thirty three households with 84 TB patients were identified between February 1993 and April 1996 and the transmission of TB was studied by combining Mycobacterium tuberculosis fingerprinting with in depth sociological interviews. RESULTS: Forty two strain genotypes were identified in the 84 patients. In 15 households all the patients had identical strains, in nine households all the patients had different strains, and in nine households some patients had identical strains and one had a different strain. In 26 houses at least one patient had a strain which formed part of a larger community cluster and in 12 of these households the patient(s) had contact with a community member who had the identical strain. In 58% of the cases the contact took place while drinking in social groups. CONCLUSION: In high incidence areas contact outside the household may be important for the transmission of TB. This contact often takes place during recreation which, in the case of this study of impoverished people, consisted of drinking in social groups. Social interaction patterns should be studied and understood for effective implementation of control strategies.